ABC transporters in CSCs membranes as a novel target for treating tumour relapse - LAURA eZINZI; Marialessandra eContino; Mariangela eCantore; Elena eCapparelli; Marcello eLeopoldo; Marcello eLeopoldo; Nicola Antonio Colabufo; Nicola Antonio Colabufo (Frontiers Media S.A., 2014)
CSCs are responsible for the high rate of recurrence and chemoresistance of different type of cancers. The current antineoplastic agents, able to inhibit bulk replicating cancer cells and radiation treatment, were found inefficacious towards CSCs since this subpopulation has several intrinsic mechanisms of resistance. Among these mechanisms, the expression of ATP-Binding Cassette (ABC) transporters family and the activation of different signaling pathway (such as Wnt/β-catenin signaling, Hedgehog, Notch, Akt/PKB) are reported. Therefore, considering ABC transporters expression on CSCs membranes, compounds able to modulate MDR could induce cytotoxicity in these cells disclosing an exciting and alternative strategy for targeting CSCs in tumour therapy. The next challenge in the cure of cancer relapse may be a multimodal strategy, an approach in which specific CSCs targeting drugs exert simultaneously the ability to circumvent tumor drug resistance (ABC transporters modulation) and cytotoxic activity towards CSCs and the corresponding differentiated tumour cells. The efficacy of suggested multimodal strategy could be probed by using several scaffolds active towards MDR pumps on CSCs isolated by tumour specimens.